Study of the effect of Ca, Fe and Zn content on the recovery of phytic acid in infant cereals with the HPLC - RI Method . Problems and solutions - Amaro Fernandes, Rosa María; Caripá Bravo, Dilia Carolina; Mijares Echezuria, Eloy Guillermo; Salas Acosta, Daniela; Gómez, Luis Ramón; Murillo Araque, Migu el íngel; Escalona Trompis, Andrés Alfredo (Ciencia, 2016)
Phytic acid is an antinutrient that inhibits metal/mineral absorption, affecting the nutrition of infants. The high performance liquid chromatography with refractive index (HPLC-RI) has been the commonly used technique for the determination of phytic acid (IP6) in infant cereals. Despite numerous studies, the low phytic recovery still affecting theaccuracy of the determination. In this paper, a HPLC-RI methodology was optimized focusing on the factors that may affect the accuracy of the method. The results indicate that infant cereals, usually having high mineral content, present recoveries in a range from 48 to 57% that significant contrast with the approximately 92% recoveries obtained with grains wheat whose mineral content is low. It seems that insufficient recoveries are produced by the precipitation of the phytic acid during the extraction process, induced by the mineral content in the infant cereal. The efficiency of recovery of phytic acid in presence Fe and Ca was improved by the use of trichloroacetic acid. This recovery depends of concentration of phytic acid in the sample. Zn was not considered in this study because all the cereals under study presented similar concentratio